PROJECT ACTIVITIES IN THE PROCESS OF TRAINING FUTURE SPECIALISTS OF THE AUTOMOTIVE INDUSTRY - Макиевский, Алексей (SWorldJournal, 2021)
The article is devoted to the search for effective methods of organizing the educational process within the training of future specialists in the automotive industry. The study notes that the problem of forming professional competencies of future special